Endoscopic Endonasal Management of Recurrent Petrous Apex Cholesterol Granuloma - McLaughlin, Nancy; Kelly, Daniel F.; Prevedello, Daniel M.; Shahlaie, Kiarash; Carrau, Ricardo L.; Kassam, Amin B. (Journal of Neurological Surgery Part B: Skull Base, 2012)
Introduction Petrous apex cholesterol granulomas (PACGs) are uncommon lesions. Recurrence following transcranial or endonasal approaches to aerate the cyst occurs in up to 60% of cases. We describe the technical nuances pertinent to the endonasal endoscopic management of a recurrent symptomatic PACG and review the literature.Results A 19-year-old woman presented with a recurrent abducens nerve paresis. Four months prior, she underwent an endonasal transsphenoidal surgery (TSS) for drainage of a symptomatic PACG. Current imaging documented recurrence of the right PACG. Transsphenoidal and infrapetrous approaches were performed to obtain a wider bony opening along the petrous apex and drain the cyst. A Doyle splint was inserted into the cyst's cavity and extended out into the sphenoid sinus, maintaining patency during the healing process. Three months after surgery, the splint was removed endoscopically, allowing visualization of a patent cylindrical communication between both aerated cavities. The patient remains symptom-free and recurrence-free.Conclusion Endoscopic endonasal surgery must be adapted to manage a recurrent PACG. A TSS may not be sufficient. An infrapetrous approach with wider bony opening, extensive removal of the cyst's anterior wall, and the use of a stent are indicated for the treatment of recurrent PACG and to prevent recurrences.
Keywords: cholesterol granuloma; petrous apex; endoscopy; transsphenoidal approach; expanded endonasal approach